The terms are in descending order, so a = 4, b = -35, and c = -9.
find 2 numbers that when multiplied give you a * c (which is 4 * -9 = -36) and when added give you b (which is -35).
Try -36 and 1. When multiplied they equal -36, and when added they equal -35. Voila!
So split the middle term using the two numbers just found.
4x^2 + (-36x + 1x) - 9 = 0
Now factor by grouping. Remove the parentheses and factor out the GCF from the first 2 and the last 2 terms.
4x(x - 9) + 1(x - 9) = 0
Now factor out the GCF of the two terms.
(4x + 1)(x - 9) = 0
If 2 numbers multiplied together equal 0, then one or both of the numbers must equal 0.
4x + 1 = 0 and/or x = 9 = 0
take it from there.
how do you factor 4x^2-35x-9=0?
2 answers
ok thanks..